16MnCr5 gear shaft fracture caused by inclusions and heat treatment process. (August 2021) - Cai, Sai; Sun, Jinquan; He, Qingkun; Shi, Tong; Wang, Dongrui; Si, Jinwei; Yang, Jie; Li, Fujie; Xie, Kun; Li, Min
Highlights: The surface hardness of carburizing quenching hardening layer is low. Non-martensite microstructure is formed after heat treatment. The presence of inclusions reduces the mechanical and fatigue properties of the steel. The gear shaft is ductile fracture. Abstract: Gear shaft of 16MnCr5 steel is an important moving part to transfer torque in truck steering, which fatigue design life is 50, 000 times. However, the lifetime of the test results is only about half in two design life. The microstructure, slag inclusion, phase composition and microhardness profiles of failure gear shaft were characterized by the optical microscope, scanning electron microscope and microhardness tester, respectively. The results show that cracks appeared at the fillet of the top, pitch circle and root of the gear. The size and distribution of slag inclusions in16MnCr5 steel also have a certain effect on the initiation of surface cracks of gears. The surface hardness of carburizing quenching hardening layer is low. After the heat treatment, a non-martensitic microstructure is formed, and machining hardening occurs on the right tooth surface, which seriously affects the contact fatigue degree of the gear.